Study on fault diagnostic strategy under unreliable test - Dong, Haidi; He, Bing; Liu, Gang; He, Huafeng; Qi, Haozhen; Ji, Yiwei (Chinese Control Conference, 2016)
A new diagnostic strategy for complex system under unreliable test is proposed. Firstly, a system mean detection cost function is established to evaluate the test cost and misdiagnosis price at the same time. Then a Rollout algorithm based on information entropy theory is proposed, which takes an average detection cost as the heuristic evaluation function. Simulation case and engineering example verify the proposed method. Results show that the proposed algorithm meets the requirements for high search speed and acceptable test cost in engineering application.